"A Slavery of Intellect and Morals:" The Scopes Trial, Dean Henry H. Rusby, and University Admission. Issue 2 (3rd May 2016) - Wechsler, Harold S.
ABSTRACT: "The freedom of a university to make its own judgments as to education includes the selection of its student body, " stated Supreme Court Justice Felix Frankfurter in 1957. During the 1925 Scopes trial, Columbia Pharmacy Dean Henry H. Rusby asserted that colleges should reject the entrance credentials of students taught the Biblical viewpoint on creation. For the next century, college officials worked to make evolution the fundamental basis for postsecondary—and high school—work in biology. A 2006 challenge to University of California entrance requirements established the university's right to reject the credentials of applicants from schools using creationist biology textbooks, as Rusby desired.